Reconsolidation-induced memory persistence: Participation of late phase hippocampal ERK activation - Krawczyk, Maria del Carmen (2016)
Persistence is an attribute of long-term memories (LTM) that has recently caught researcher's attention in search for mechanisms triggered by experience that assure memory perdurability. Up-to-date, scarce evidence of relationship between reconsolidation and persistence has been described. Here, we characterized hippocampal ERK participation in LTM reconsolidation and persistence using an inhibitory avoidance task (IA) at different time points. Intra-dorsal-hippocampal (dHIP) administration of an ERK inhibitor (PD098059, PD, 1.0 μg/hippocampus) 3 h after retrieval did not affect reconsolidation of a strong IA, when tested 24 h apart. However, the same manipulation impaired performance when animals were tested at 7 d, regardless of the training's strength; and being specific to memory reactivation. To the best of our knowledge, this is the first report showing that persistence might be triggered after memory reactivation involving an ERK/MAPK-dependent process.